Commercially available granulates PMMA and PS - potential problems with the production of polymer optical fibers - Jóźwicki, Mateusz Łukasz; Gargol, Mateusz; Gil-Kowalczyk, Małgorzata; Mergo, Paweł (Photonics Letters of Poland, 2020)
The aim of the study was to verify the usefulness of commercially available granulates of PMMA (poly (methyl methacrylate) and PS (polystyrene) for the production of polymer optical fibers by extrusion method. Samples were subjected to thermal processing in various conditions (different temperatures and exposure time). Thermal (TG/DTG) and spectroscopic (ATR/FT-IR) analyses were carried out to analyze changes in the samples. Based on FT-IR analysis of liquid monomers and granulates the conversion of double bonds was calculated, which gave us a picture of the degree of monomers conversion, crucial information from the technological point of view. Full Text: PDF References O. Ziemann, J. Krauser, P.E. Zamzow, W. Daum, POF Polymer Optical Fibersfor Data Communication (Berlin: Springer 2008). DirectLink P. Stajanca et al. "Solution-mediated cladding doping of commercial polymer optical fibers", Opt. Fiber Technol. 41, 227-234, (2018). CrossRef K. Peters, "Polymer optical fiber sensors—a review", Smart Mater. Struct., 20 013002 (2011) CrossRef J. Zubia and J. Arrue, "Plastic Optical Fibers: An Introduction to Their Technological Processes and Applications", Opt. Fiber Technol. 7 ,101-40 (2001) CrossRef M. Beckers, T. Schlüter, T. Gries, G. Seide, C.-A. Bunge, "6 - Fabrication techniques for polymer optical fibres", Polymer Optical Fibres, 187-199 (2017) CrossRef M. Niedźwiedź , M. Gil, M. Gargol , W. Podkościelny, P. Mergo, "Determination of the optimal extrusion temperature of the PMMA optical fibers", Phot. Lett. Poland 11, 7-9 (2019) CrossRef